2017
DOI: 10.3390/cryst7120384
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Epitaxial Crystallization on the Mechanical Properties of Polyamide 66/Reduced Graphene Oxide Nanocomposite Injection Bar

Abstract: Polyamide 66 (PA66) was chosen as the representative of hydrophilic polymers, to investigate the influence of epitaxial crystals in semi-crystalline polymers/reduced graphene oxide nanocomposite injection-molding bars. A differential scanning calorimeter was used, and the two-dimensional wide-angle X-ray diffraction technique, as well as the two-dimensional small angle X-ray scattering technique, were used to research the crystallization behavior in PA66/RGO nanocomposites. The results indicated that RGO was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 47 publications
1
13
0
Order By: Relevance
“…Because of the addition of RGO, the unstretched sample possesses orientation. 20 As can be seen in Figure 3 , the nonuniform diffraction ring of the (010) + (110) lattice plane becomes more focused and the elliptic 2D SAXS signal is stretched during the stretching process. In Figure 4 a, the positions of WAXD peaks do not change, indicating that the crystal form of PA66 is maintained during the elastic deformation process.…”
Section: Resultsmentioning
confidence: 93%
See 3 more Smart Citations
“…Because of the addition of RGO, the unstretched sample possesses orientation. 20 As can be seen in Figure 3 , the nonuniform diffraction ring of the (010) + (110) lattice plane becomes more focused and the elliptic 2D SAXS signal is stretched during the stretching process. In Figure 4 a, the positions of WAXD peaks do not change, indicating that the crystal form of PA66 is maintained during the elastic deformation process.…”
Section: Resultsmentioning
confidence: 93%
“…The Lorentz-corrected 1D SAXS curves of pure PA66 only have one slight peak located at the q 2 position ( q 2 peak) throughout the stage I ( Figure 2 b), which accords with our previous work which indicated that the scattering peak of the pure PA66 sample is at q = 0.80 nm –1 . 20 Although we only obtain the partial q 2 peak, its variation trend can be distinguished. With the increase of strain, the peak intensity of the q 2 position continually slightly increases and the q 2 peak slightly moves toward a lower q value.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Graphene oxide (GO), including reduced graphene oxide (RGO) and thermally reduced GO (TRGO), is typical graphene materials with topological defects in their periodic structures [150,151], shown in Figure 16. GO exhibited an extra Raman peak below the G band (about 1600 cm −1 ) in Figure 16b, which was ascribed to the oxidation of graphite and the subsequent introduction of defects in the graphitic planes.…”
Section: Graphene Oxidementioning
confidence: 99%